Impact of Risk-Adapted Therapy for Pediatric Hodgkin Lymphoma on Risk of Long-Term Morbidity: A Report From the Childhood Cancer Survivor Study. Issue 20 (10th July 2021) - Oeffinger, Kevin C.; Stratton, Kayla L.; Hudson, Melissa M.; Leisenring, Wendy M.; Henderson, Tara O.; Howell, Rebecca M.; Wolden, Suzanne L.; Constine, Louis S.; Diller, Lisa R.; Sklar, Charles A.; Nathan, Paul C.; Castellino, Sharon M.; et al.
Abstract : PURPOSE: To determine the incidence of serious chronic health conditions among survivors of pediatric Hodgkin lymphoma (HL), compare by era of therapy and by selected cancer therapies, and provide estimates of risks associated with contemporary therapy. METHODS: Assessing 2, 996 5-year HL survivors in the Childhood Cancer Survivor Study diagnosed from 1970 to 1999, we examined the cumulative incidence of severe to fatal chronic conditions (grades 3-5) using self-report conditions, medically confirmed subsequent malignant neoplasms, and cause of death based on the National Death Index. We used multivariable regression models to estimate hazard ratios (HRs) per decade and by key treatment exposures. RESULTS: HL survivors were of a mean age of 35.6 years (range, 12-58 years). The cumulative incidence of any grade 3-5 condition by 35 years of age was 31.4% (95% CI, 29.2 to 33.5). Females were twice as likely (HR, 2.1; 95% CI, 1.8 to 2.4) to have a grade 3-5 condition compared with males. From the 1970s to the 1990s, there was a 20% reduction (HR, 0.8; 95% CI, 0.7 to 0.9) in decade-specific risk of a grade 3-5 condition ( P trend = .002). In survivors who had a recurrence and/or hematopoietic cell transplant, the risk of a grade 3-5 condition was substantially elevated, similar to that of survivors treated with high-dose, extended-field radiotherapy (HR, 1.2; 95% CI, 0.9 to 1.5). Compared with survivors treated with chest radiotherapy ≥ 35 Gy in combination with an anthracycline or alkylator, a contemporary regimen for low-intermediate risk HL was estimated to lead to a 40% reduction in risk of a grade 3-5 condition (HR, 0.6; 95% CI, 0.4 to 0.8). CONCLUSION: This study demonstrates that risk-adapted therapy for pediatric HL has resulted in a significant reduction in serious long-term outcomes.